Overexpression of the androgen receptor in human hepatoma cells and its effect on fatty acid metabolism - Kanda, Tatsuo (Oncol Lett, 2017)
Hepatocellular carcinoma (HCC) is a predominantly male disease in which the androgen receptor (AR) serves an important pathogenic role in hepatocarcinogenesis. Fatty acid metabolism also contributes to hepatocarcinogenesis and is associated with the prognosis of cancer. The present study aimed to investigate the effects of the AR on fatty acid metabolism-associated gene expression in human hepatoma cell lines. AR-expression plasmids or control plasmids were transiently transfected into the human HCC cell lines Huh7 and HepG2. After 48 h, cellular protein and RNA were extracted and the expression of AR was confirmed by western blotting. Complementary DNA was synthesized and subjected to a quantitative polymerase chain reaction-based array to examine the expression of 84 fatty acid metabolism-associated genes. Overexpression of AR significantly downregulated the expression of 11 fatty acid metabolism-associated genes in Huh7 cells and 35 in HepG2 cells. The overexpression of AR also resulted in the upregulation of 6 fatty acid metabolism genes in HepG2 cells; however, it had no effect in Huh7 cells. Acyl-coenzyme A (CoA) thioesterase 7 and acyl-CoA oxidase 3 were downregulated in both cell lines. In conclusion, upregulation of AR via overexpression led to the disturbance of fatty acid metabolism-associated gene expression in human HCC cells. Therefore, the AR may serve a role in hepatocarcinogenesis via the regulation of hepatocellular fatty acid metabolism.